Training On How To Enlarge Dendrobium Orchids From Seedling Pots Using The Semi Hydroponic Method In Punggur Kecil Village, Kubu Raya Regency - Zulfita, Dwi; Budi, Setia; Surachman, Surachman; Hariyanti, Agus (International Journal of Public Devotion, 2023)
Punggur Kecil village, Kubu Raya district, is represented by its poor people who depend on agriculture as it is. Most of the community are Malays living in the village with a very narrow land area, making it impossible to carry out agricultural cultivation that requires a large scale of land. The problem faced by the Dasa Wisma Kenanga women's group is that they rely on their life by taking orchid species in the forest and farming as it is. This is done because the family's income from selling cultivated vegetables is uncertain, especially during the rainy season and fluctuations in the price of vegetables which have recently declined and are sometimes not marketed. The activity results show that the level of material acceptance is excellent. The majority of 67% of participants can understand the material. The level of understanding in how to grow orchids from seedling pots using the semi-hydroponic method was divided into 68% understanding, 27% very understanding, and only 5% stating a little experience. Continuation of the program, 70% of participants want it. Overall, the participants liked the semi-hydroponic orchid enlargement method, with 27% preferring semi-hydroponic orchids, 14% preferring ordinary orchid cultivation, and 64% picking the combination of both.